What is the predictive value of MRI for the occurrence of knee replacement surgery in knee osteoarthritis?. Issue 10 (25th July 2013) - Pelletier, J-P; Cooper, C; Peterfy, C; Reginster, J-Y; Brandi, M-L; Bruyère, O; Chapurlat, R; Cicuttini, F; Conaghan, P G; Doherty, M; Genant, H; Giacovelli, G; et al.
Abstract : Knee osteoarthritis is associated with structural changes in the joint. Despite its many drawbacks, radiography is the current standard for evaluating joint structure in trials of potential disease-modifying osteoarthritis drugs. MRI is a non-invasive alternative that provides comprehensive imaging of the whole joint. Frequently used MRI measurements in knee osteoarthritis are cartilage volume and thickness; others include synovitis, synovial fluid effusions, bone marrow lesions (BML) and meniscal damage. Joint replacement is considered a clinically relevant outcome in knee osteoarthritis; however, its utility in clinical trials is limited. An alternative is virtual knee replacement on the basis of symptoms and structural damage. MRI may prove to be a good alternative to radiography in definitions of knee replacement. One of the MRI parameters that predicts knee replacement is medial compartment cartilage volume/thickness, which correlates with radiographic joint space width, is sensitive to change, and predicts outcomes in a continuous manner. Other MRI parameters include BML and meniscal lesions. MRI appears to be a viable alternative to radiography for the evaluation of structural changes in knee osteoarthritis and prediction of joint replacement.